The Effectiveness of Installing Long-lasting Insecticidal Nets as Malaria Prevention Efforts: A Systematic Literature Review - Nurhayani; Dyah Farida Inli; Riandini Aisyah; Rochmadina Suci Bestari (Open Access Indonesian Journal of Medical Reviews, 2022)
Malaria is a parasitic disease that is often the cause of death, especially in tropical and subtropical areas. One way to eradicate malaria is to break the chain of disease transmission in order to control the mosquito vector of malaria. The use of insecticide-treated mosquito nets can be used as an alternative in controlling malaria vectors for people who refuse to use the Indoor Residual Spraying (IRS) method. The review articles were obtained through a search using the Pubmed, Google Scholar, Garuda, and ScienceDirect databases. The keywords used were (LLINs OR "Long Lasting Insecticidal Nets") AND Malaria. 1843 articles were obtained, and extraction was carried out based on the restriction criteria so that 13 articles were obtained. In conclusion, the use of insecticide-treated mosquito nets LLIN is effective in killing mosquito vectors so that it has the potential to prevent malaria.